Students’ perceptions on lexical bundle mobile application for group discussion / Muhamad Izzat Rahim and Nur' Ain Zuraimi - Rahim, Muhamad Izzat; Zuraimi, Nur' Ain (UiTM Cawangan Negeri Sembilan, 2022)
Group discussion is an important discourse for students in universities and colleges. It is used widely for pedagogical and assessment purposes especially in English language classes. Albeit the important status, some students are struggling with group discussion. It is suggested for the students to be equipped with relevant lexical bundles. As such this study aims to present the perceptions of sixteen undergraduate students on the usage of lexical bundle mobile application. They were instructed to complete a task using the application. Later, their perceptions towards the application were recorded. Thematic analysis was used to analyse the feedbacks. Three themes emerged from the analysis of feedbacks namely benefits, usage, and recommendations. It was found that majority of the students viewed the utilisation of the lexical bundle mobile application as beneficial. Similarly, many of them said that the application was easy to be used. Although there were negative feedbacks on the usage, it only represented a little percentage from the total number of the students. Additionally, the students provided constructive recommendations for future improvement. In brief, the findings of this study could be used as reference for the development and usage of lexical bundle mobile application as mobile application could be one of the instruments utilised in language classes.